Checklist of the vascular flora of Reserva Biológica San Luis, Costa Rica - Jiménez-Alfaro, Esteban José (2016)
The Reserva Biológica San Luis is a small protected area located on the Pacific side of the Cordillera de Tilarán, northwestern Costa Rica, with a forest transitioning between the basal and premontane floras according to Holdridge’s Life Zones. An inventory of the vascular flora of the reserve was performed by collecting botanical samples during three years and consulting the databases of the CR, INB, MO and USJ herbaria. We report 130 families, 477 genera and 716 species of native vascular plants. Angiosperms comprise the largest group with 94.3%, followed by Pteridophytes 5.4% and Lycophytes 0.3%. The best represented life forms are herbaceous and arborescent with 35.7% and 26.8% respectively. Fabaceae and Piper are the most diverse family and genus, with 67 and 15 species respectively. Despite occupying 0.000049% of the total area of Costa Rica, this reserve protects approximately 7.3% of the vascular plants of the country.